On Workified Education and the Possibility of Leisure - Zipory, Oded (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
The article is concerned with the difficulty of providing leisure today with a positive definition that goes beyond merely being a negation of work. I argue that the vague boundaries between work and leisure play into the hands of work – a highly praised activity that is dominant in today’s society. I argue that in such a situation, education as leisure and as good in itself is hard to conceive and sustain. First, I present the concept of leisure in ancient Greece (scholé) as time dedicated to autotelic activities – activities taken for their own good – a definition that remains paradigmatic despite its later impossibility. I then show that once work has transformed from hated to bearable to eventually understood as good from a moral perspective, the concept of leisure has also changed – so much so that its positive definition is no longer available to us. After showing how education is affected by the diffusion of the boundaries between work and leisure, I suggest three possible ways to counter this process: (1) focusing on leisure as resistance to the dominance of work, (2) appealing to the deep connection between leisure and religious worship, and (3) a radical rejection of the concept of “leisurely work” or any other kind of work that is presumed good in itself.